Comparative Study Of Deep Cervical Flexion Exercise With Pressure Biofeedback and Muscle Energy Technique for Neck Pain Reduction in Digital Workers - Ayu Feratywi; Susy Purnawati; Wahyuddin Wahyuddin (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Mechanical neck pain is a common condition among employees who perform static tasks in non-ergonomic postures while using digital devices, potentially leading to pain, disability, and reduced work productivity. The purpose of this study to prove that deep cervical flexion exercise with pressure biofeedback is more effective than muscle energy technique in reducing neck pain and disability in mechanical neck pain conditions of digital creative employees. This study is a true experiment with pre-test and post-test two group design. The subjects of the study were 24 people who were randomly divided into two groups. Group 1 (n=12) received deep cervical flexion exercise with pressure biofeedback, while group 2 (n=12) received muscle energy technique. Pain intensity was measured using the numeric pain rating scale and neck disability was assessed using the neck disability index. The results of the paired sample t-test showed a significant reduction in pain and disability in both groups (p=0.001; p<0.05). The independent sample t-test confirmed significant differences between the groups (p<0.05), with group 1 showing a greater percentage reduction in both pain (68.40%) and disability (55.48%) compared to group 2 (44% and 30.55%). In conclusion, deep cervical flexion exercise with pressure biofeedback showed greater improvement compared to muscle energy technique in reducing neck pain and disability in mechanical neck pain conditions of digital creative employees. Although limited by age differences between groups as a potential confounding factor, the findings remain applicable to workers with prolonged static and non-ergonomic postures.